Donepezil for dementia with Lewy bodies: a randomized, placebo-controlled, confirmatory phase III trial - Ikeda, Manabu (Alzheimers Res Ther, 2015)
INTRODUCTION: The efficacy of a cholinesterase inhibitor, donepezil, in patients with dementia with Lewy bodies (DLB) was investigated to confirm the superiority over placebo in the 12-week, double-blind phase of this phase III study. METHODS: Patients with probable DLB (n = 142) were randomly assigned to placebo or to 5 mg or 10 mg of donepezil administered once daily for 12 weeks. The co–primary endpoints were changes in cognitive function assessed using the Mini-Mental State Examination (MMSE) and behavioral and neuropsychiatric symptoms using the Neuropsychiatric Inventory (NPI-2: hallucinations and fluctuations). The superiority of each active group over placebo was determined with simultaneous statistical significance in both endpoints. Safety evaluations included adverse events (AEs) and the unified Parkinson's disease rating scale (UPDRS) part III. RESULTS: The predefined superiority of donepezil to the placebo was not confirmed in either active group in the primary analysis. MMSE score significantly improved compared to placebo in the 10 mg group (10 mg: 2.2 ± 0.4, placebo: 0.6 ± 0.5 (mean ± standard error); P = 0.016). The change in MMSE score in the 5 mg group was not significant (1.4 ± 0.5 (mean ± standard error); P = 0.232). Although NPI-2 improved compared to baseline in the active groups, the differences from placebo were not significant. Most AEs were mild or moderate. Although the incidence of parkinsonism was slightly higher in the 10 mg group, the change in the UPDRS score was minimal and without a significant difference from the placebo group. CONCLUSIONS: The co–primary endpoints were not achieved in this trial. However, significant improvement in MMSE score was demonstrated with 10 mg, but not 5 mg, of donepezil. The evaluation of psychiatric symptoms might be affected by advanced education and instructions given to caregivers. Overall, donepezil was well tolerated in patients with DLB. With careful attention on gastrointestinal or parkinsonian symptoms, patients with DLB can safely benefit from treatment with donepezil. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01278407 (trial registration date: 14 January 2011) ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13195-014-0083-0) contains supplementary material, which is available to authorized users.